Combustion characteristics of biomass in SouthEast Asia - Aghamohammadi, N.; Sulaiman, Nik Meriam Nik; Aroua, M.K. (Elsevier, 2011)
Gas emission during combustion of mixed tropical wood, bamboo, oil palm trunk, acacia, and rubber wood have been investigated by using TG-MS in presence of oxygen as well as FTIR. The weight decreasing profiles and the gas formation rates of oil palm trunk was significantly different among the samples although their elemental composition was almost the same from biomass samples. It was found that H(2)O is the main product formed for all samples. The evolving rates of the gaseous products during the combustion and infrared spectrums such as CO, H(2)O, CO(2), CH(4) and COOH(+) were found. The DTG curves spectrums for biomass present four overlapping peaks.